1995
DOI: 10.1103/physrevb.52.13711
|View full text |Cite
|
Sign up to set email alerts
|

Spectral weight transfer and mass renormalization in Mott-Hubbard systemsSrVO3andCaVO3

Abstract: We have studied metallic SrVO3 and CaVO3 by inverse photoemission and high-resolution photoemission. In going from Sr to Ca, considerable spectral weight is transferred from the coherent band to the upper and lower Hubbard bands. Meanwhile, the overall intensity rather than the width of the coherent band decreases, implying that the bandwidth remains finite as the system approaches the Mott transition. The result implies that the e6'ect of long-range Coulomb interaction as well as short-range interaction becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
122
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(135 citation statements)
references
References 18 publications
11
122
2
Order By: Relevance
“…On the other hand, PES [14], seemed to imply dramatic differences between CaVO 3 and SrVO 3 , with CaVO 3 having (almost) no spectral weight at the Fermi energy. Rozenberg et al [15] interpreted these results in terms of the (DMFT) Mott-Hubbard transition in the half-filled single-band Hubbard model.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, PES [14], seemed to imply dramatic differences between CaVO 3 and SrVO 3 , with CaVO 3 having (almost) no spectral weight at the Fermi energy. Rozenberg et al [15] interpreted these results in terms of the (DMFT) Mott-Hubbard transition in the half-filled single-band Hubbard model.…”
Section: Introductionmentioning
confidence: 99%
“…In Sr 2 IrO 4 , it has been reported that Mott insulator develops due to the strong spin-orbit interaction of Ir 5d-electrons [9]. In addition, it has been well known that the physics of the Mott insulating states plays an important role to understand the metallic peroskite CaVO 3 and SrVO 3 [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Based on our electronic structure calculations (discussed in detail below) and comparison with chemically similar model compounds, 60,61,62,63,64 we assign the features centered at ∼1 and 2.3 eV to nearly spin-polarized V 4+ d → d on-site excitations in the majority spin channel. The 1 eV feature blueshifts with decreasing temperature and is sensitive to the 110 K structural phase transition.…”
Section: Resultsmentioning
confidence: 99%